2020
DOI: 10.3390/biom10010080
|View full text |Cite
|
Sign up to set email alerts
|

From Translation to Protein Degradation as Mechanisms for Regulating Biological Functions: A Review on the SLRP Family in Skeletal Tissues

Abstract: The extracellular matrix can trigger cellular responses through its composition and structure. Major extracellular matrix components are the proteoglycans, which are composed of a core protein associated with glycosaminoglycans, among which the small leucine-rich proteoglycans (SLRPs) are the largest family. This review highlights how the codon usage pattern can be used to modulate cellular response and discusses the biological impact of post-translational events on SLRPs, including the substitution of glycosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 170 publications
0
22
0
Order By: Relevance
“…Majority of ECM components are the proteoglycans, among which the SLRPs are the largest family 31 . SLRPs are capable of clustering different types of receptors and affecting downstream intracellular phosphorylation events, including those driven by TGF-beta/BMP superfamily members, epidermal growth factor receptors, insulin like growth factor I receptors, Met receptor and Toll-like receptors 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Majority of ECM components are the proteoglycans, among which the SLRPs are the largest family 31 . SLRPs are capable of clustering different types of receptors and affecting downstream intracellular phosphorylation events, including those driven by TGF-beta/BMP superfamily members, epidermal growth factor receptors, insulin like growth factor I receptors, Met receptor and Toll-like receptors 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Decorin, biglycan, fibromodulin, lumican, PRELP (proline-arginine-rich-end-leucine-rich repeat protein), chondroadherin, and osteoadherin are members of the small leucine-rich repeat protein (SLRP) family, as reviewed by Zappia et al ( 31 ). Fibromodulin is a keratan sulfate proteoglycan found in cartilage and tendon.…”
Section: Extracellular Damage-associated Molecular Patterns From Cartmentioning
confidence: 99%
“…Although lumican belongs to the SLRP family and may therefore be involved in bone metabolism [5], the effects of lumican on bone biology are not yet fully understood. In vitro and animal experiments have demonstrated that lumican promotes preosteoblast viability and differentiation via integrin α2β1 and downstream ERK signaling, leading to bone formation [14].…”
Section: Inhibition Of In Vitro Bone Resorption and Osteoclastogenesis By Lumican Treatmentmentioning
confidence: 99%
“…SLRPs directly or indirectly regulate multiple cellular processes through interactions with various growth factors, cytokines, cell surface receptors, and other ECM components [ 4 ]. Importantly, most SLRPs are enriched in skeletal tissues [ 5 ], and several lines of evidence indicate that specific SLRPs play critical roles in bone homeostasis [ 6 , 7 ]. For example, mice lacking biglycan, a class I SLRP, exhibit osteoporotic phenotypes caused by a reduction in new bone formation and an increase in osteoclastogenesis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation